Insect–microbe interactions and their influence on organisms and ecosystems - Jocelyn R. Holt; Nathalia Cavichiolli de Oliveira; Raul F. Medina; Antonino Malacrinò; Amelia R. I. Lindsey (Ecology and Evolution)
Abstract Microorganisms are important associates of insect and arthropod species. Insect‐associated microbes, including bacteria, fungi, and viruses, can drastically impact host physiology, ecology, and fitness, while many microbes still have no known role. Over the past decade, we have increased our knowledge of the taxonomic composition and functional roles of insect‐associated microbiomes and viromes. There has been a more recent shift toward examining the complexity of microbial communities, including how they vary in response to different factors (e.g., host genome, microbial strain, environment, and time), and the consequences of this variation for the host and the wider ecological community. We provide an overview of insect–microbe interactions, the variety of associated microbial functions, and the evolutionary ecology of these relationships. We explore the influence of the environment and the interactive effects of insects and their microbiomes across trophic levels. Additionally, we discuss the potential for subsequent synergistic and reciprocal impacts on the associated microbiomes, ecological interactions, and communities. Lastly, we discuss some potential avenues for the future of insect‐microbe interactions that include the modification of existing microbial symbionts as well as the construction of synthetic microbial communities.